1971
DOI: 10.1073/pnas.68.11.2757
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adenosine 3′:5′-Cyclic Monophosphate Concentration in Cultured Human Astrocytoma Cells by Catecholamines and Histamine

Abstract: Norepinephrine, epinephrine, and histamine cause a rapid increase in the concentration of adenosine 3':5'-cyclic monophosphate (cAMP) in a tumor astrocyte cell line derived from a primary culture of a human glioblastoma multiforme. The catecholamine-induced increase in cAMP is dependent on the cell density, being far greater in cells in the log phase of growth than in cells near terminal density. The response to norepinephrine is inhibited 50% by 0.01 pM propranolol, a blocking agent of #-adrenergic receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(35 citation statements)
references
References 12 publications
(10 reference statements)
4
31
0
Order By: Relevance
“…It had no effect on theophylline-induced inhibition of thymidine uptake, and indeed, in neuronal cells theophylline has been reported to be an inhibitor of adenosine-mediated elevations of cyclic AMP concentrations (11,23). Taken alone, these results suggest that adenosine deaminase inhibition can augment the effects of cyclic AMP.…”
Section: Discussionmentioning
confidence: 51%
“…It had no effect on theophylline-induced inhibition of thymidine uptake, and indeed, in neuronal cells theophylline has been reported to be an inhibitor of adenosine-mediated elevations of cyclic AMP concentrations (11,23). Taken alone, these results suggest that adenosine deaminase inhibition can augment the effects of cyclic AMP.…”
Section: Discussionmentioning
confidence: 51%
“…There is evidence that adenosine stimulates adenylate cyclase leading to elevated cyclic AMP levels in brain tissue slices (Sattin & RalL 1970;Schultz & Daly, 1973) and nerve cells in tissue culture (Clark et al, 1974;Blume & Foster, 1975). Since an increase in cyclic AMP is associated with acetylcholine release (Goldberg & Singer, 1969;Wilson, 1974), it seems unlikely, on circumstantial grounds, that this mechanism operates in the adenine-induced inhibition of acetylcholine release that we have documented.…”
Section: Discussionmentioning
confidence: 99%
“…These include suggestions that adenosine, adenosine 5'-pyrophosphate (ADP) and adenosine 5'-triphosphate (ATP) function as neurotransmitters released by inhibitory 'purinergic' nerve endings (Burnstock, CampbelL Satchell & Smythe, 1970;Burnstock, 1972;Satchell & Burnstock, 1975;Okwuasaba, Hamilton & Cook, 1977); that their action is mediated by alterations in intracellular levels of cyclic adenosine 3',5'-monophosphate (cyclic AMP) (Sattin & Rall, 1970;Clark, Gross, Su & Perkins, 1974); or that they affect the passage of sodium (Imai Since calcium ions are critically and ubiquitously involved in the function of excitable cells, we have studied the effects of adenosine and adenine derivatives on contractile responses of the guinea-pig ileum longitudinal muscle-myenteric plexus preparation at different calcium concentrations. Our results have shown that adenosine-containing compounds act at a presynaptic site on postganglionic cholinergic neurones in the myenteric plexus and that this action may be mediated by modulation of intra-axonal calcium concentration.…”
Section: Introductionmentioning
confidence: 99%
“…ATP, after breakdown to adenosine, increases intracellular cAMP in human 1321NI astrocytoma cells [633,634]. However, later papers showed that high concentrations of ATP, acting via P2 receptors, stimulate proliferation of SKMG-1 and U373 human astrocytoma cells [635] or inhibition of proliferation of 132NI astrocytoma cell [636].…”
Section: Gliomasmentioning
confidence: 99%